The diagnosis, prevalence and outcome of delirium in a cohort of older people with mental health problems on general hospital wards - Whittamore, Kathy H.; Goldberg, Sarah E.; Gladman, John R.F.; Bradshaw, Lucy E.; Jones, Rob G.; Harwood, Rowan H. (Wiley, 2013)
Keywords: older person;delirium;Delirium Rating Scale;validity;prognosis;diagnosis;general hospital Objectives This paper aimed to measure the prevalence and outcomes of delirium for patients over 70 admitted to a general hospital for acute medical care and to assess the validity of the Delirium Rating Scale-Revised-98 (DRS-R-98) in this setting.